2011
DOI: 10.1117/12.886414
|View full text |Cite
|
Sign up to set email alerts
|

Supercontinuum generation in suspended core microstructured tellurite optical fibers

Abstract: We present the fabrication of tellurite TeO 2 -ZnO-Na 2 O (TZN) microstructured optical fibers (MOFs) with a suspended core and the characterization of their optical properties. The fibers are designed to develop an infrared supercontinuum generation using a sub-nJ femtosecond pulsed laser at 1.56µm. By pumping a 20 cm long fiber we generate a supercontinuum (SC) spanning over 800 nm in the 1-2 µm wavelength range. For a MOF with a core size of 2.2 µm the zero dispersion wavelength (ZDW) is at 1.45 µm. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In recent years, several experimental and theoretical investigations on mid-infrared SC generation were reported in ChG planar waveguides [13][14][15], ChG fibers [16][17][18][19][20][21][22][23][24][25][26][27][28], single crystal sapphire fibers [29], silicon-on-insulator (SOI) wire waveguides [30], ZBLAN fiber [31], fluoride glass [32] and germano-silicate fibers [33]. Gai et al [13] reported SC generation from 2.9 µm to 4.2 µm in dispersion-engineered As 2 S 3 glass rib waveguide (6.6 cm long) pumped with 7.5 ps duration pulses at a wavelength of 3.26 µm with a pulse peak power of around 2 kW.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several experimental and theoretical investigations on mid-infrared SC generation were reported in ChG planar waveguides [13][14][15], ChG fibers [16][17][18][19][20][21][22][23][24][25][26][27][28], single crystal sapphire fibers [29], silicon-on-insulator (SOI) wire waveguides [30], ZBLAN fiber [31], fluoride glass [32] and germano-silicate fibers [33]. Gai et al [13] reported SC generation from 2.9 µm to 4.2 µm in dispersion-engineered As 2 S 3 glass rib waveguide (6.6 cm long) pumped with 7.5 ps duration pulses at a wavelength of 3.26 µm with a pulse peak power of around 2 kW.…”
Section: Introductionmentioning
confidence: 99%
“…SEM images of various tellurite glass micro structured fibers (a) core diameters varying from 1.6 to 2.2 µm. (b) the same fiber at different scales [70]. …”
mentioning
confidence: 99%
“…However, the enormous design flexibility to tailor the nonlinearity and the dispersion profile comes along with a limited spectral coverage of the wavelength region above 3 µm. [11][12][13][14] This is due to increased absorption related to…”
Section: Introductionmentioning
confidence: 99%
“…Most reports about tellurite glass fibers in the literature have been based on microstructured optical fibers pumped in the near-IR. [11][12][13][14][15] These fibers show enhanced nonlinearities due to the small core sizes and engineered zero dispersion wavelengths (ZDWs) below 2 µm, allowing for anomalous dispersion pumping with conventional laser systems. However, the enormous design flexibility to tailor the nonlinearity and the dispersion profile comes along with a limited spectral coverage of the wavelength region above 3 µm.…”
Section: Introductionmentioning
confidence: 99%